IMPLIKASI PRAKTIK MONEY POLITICS TERHADAP KEPUTUSAN PEMILIH PADA PEMILIHAN CALON ANGGOTA DPRD KABUPATEN MUSI BANYUASIN TAHUN 2024 (Studi Kasus di Dapil 1 Kecamatan Sekayu) - Yusril Mahendra,; Taufik Akhyar,; Deany Afriani, (FisiPublik: Jurnal Ilmu Sosial dan Politik, 2025)
This study aims to analyze the influence of money politics on voter decision-making in the 2024 election of DPRD (Regional People's Representative Council) candidates in Musi Banyuasin Regency, particularly in Sekayu District, as well as to evaluate the effectiveness of the socialization strategies implemented by the Election Supervisory Board (Bawaslu) in preventing such practices. Money politics remains a prevalent phenomenon in electoral contests across various regions in Indonesia, especially in areas with low political awareness and economically vulnerable communities. This research employs a descriptive qualitative approach, with data collected through in-depth interviews involving voters, political brokers, community leaders, and electoral officials in Sekayu District. The analysis is based on the theory of clientelism by Stokes (2021), which highlights transactional relationships between patrons (candidates), brokers (intermediaries), and clients (voters). Patrons offer direct benefits, such as cash or basic necessities, in exchange for political support. The findings reveal that money politics continues to be a dominant strategy in influencing voter behavior, particularly among lower-income groups. Voters often feel a moral obligation to support candidates who have provided them with tangible benefits, regardless of their knowledge of the candidate’s vision and mission. Meanwhile, Bawaslu’s socialization strategies have proven to be insufficient in effectively reaching all segments of society, particularly marginalized groups most susceptible to material inducements. The results of this study indicate that money politics significantly affects voter decisions, and preventive efforts by electoral supervisory institutions must be strengthened through more participatory and context-sensitive approaches in order to foster greater political awareness, integrity, and independence among voters.